Corporate governance and nominee directors – what does it mean? / Adam Yang Chik - Adam, Yang Chik (Universiti Teknologi MARA Cawangan Selangor, 2016)
It is a trite law that Directors are under the fiduciary duties and to act in the best interest of the company. This fundamental principle has been embedded in s.132(1E) Malaysian Companies Act 1965 (CA 1965) which codifies the responsibility of a nominee Director. The nominee directorship status poses difficulty due to dual loyalty owed by the nominee Director to the company and nominator. This raises a dilemma to nominee Directors in discharging fiduciary duties. Nominee Directors are common in the Malaysian corporate landscape. Section 132(1E) statutorily stipulate that a Director who was appointed by virtue of his position as an employee of a company and a Director who was appointed by or as a representative of a shareholder, employer or debenture holder. Nominee Directors must act in the best interest of the company. Section 132(1E) states that the nominee Director shall act in the best interest of the company and in the event of any conflict between his duty to act in the best interest of the company and his duty to his nominator, the nominee Director shall not subordinate his duty to act in the best interest of the company to his duty to his nominator. In resolving the conflict of interests and duties on nominee Directors Malaysian courts may adopt the UK strict approach. Commencing 2011 UK gradually adopted the attenuated duty approach. Malaysia with her concentrated ownership economy would adopt the attenuated duty approach. This is to ensure Malaysian corporate economy is dynamic and competitive, the approach on nominee directorships must be well established.